Cover Image, Volume 59, Issue 5. Issue 5 (4th April 2020) - Deng, Yu; Guo, Wanjun; Xu, Ning; Li, Fulun; Li, Jian
Abstract : Cover Caption : The cover image is based on the Original Article CtBP1 transactivates RAD51 and confers cisplatin resistance to breast cancer cells by Yu Deng, Fulun Li, Wanjun Guo et al., https://doi.org/10.1002/mc.23175 .